(untitled) (Educational Dimension, 2022)
The article represents methodological substantiation and results of approbation of the diagnostic tool for studying of psychological readiness of preschool age children to training at school. The presented work is a continuation of scientific research in the direction of expanding the structure of psychological readiness for school through addition of its value-semantic component, as well as creation of a tool for its measurement. In the process of developing the methodology for diagnosing the value-semantic component of the psychological readiness for learning, the author relies on the age-related psychological characteristics of a preschool age child, which are oriented toward the choice of projective technology. In addition to this, the theoretical basis for the methodology creation was the author’s vision of the content of value-semantic component of psychological readiness for learning, which constitutes an activity dynamic conceptual system of ``study``, containing a set of such values: health, active and productive life, cognition, politeness, education, tenacity. The article provides a thorough description of all the stages of the methodology development, accompanied by the results of an empirical study of its accuracy, reliability, and validity. Author’s methodology of studying the value-semantic readiness for learning contains two sets of twenty-four pictures in each according to the gender of the testee with the instruction to them. Based on the results of the methodology standardization, the forms for fixing the results of the study, as well as the decil norms for each component of the value-semantic readiness for learning (affective and cognitive), and its general index are presented.